Implementing software occlusion culling for real-time applications - Leone, Matias N. (2012)
The visualization of complex virtual scenes can be significantly accelerated by applying Occlusion Culling. In this work we introduce a variant of the Hierarchical Occlusion Map method to be used in Real-Time applications. To avoid using real objects geometry we generate specialized conservative Occluders based on Axis Aligned Bounding Boxes which are converted into coplanar quads and then rasterized in CPU using a downscaled Depth Buffer. We implement this method in a 3D scene using a software occlusion map rasterizer module specifically optimized to rasterize Occluder quads into a Depth Buffer. We demonstrate that this approach effectively increases the number of occluded objects without generating significant runtime overhead.